The Impact of Smoking on General Anesthesia: A Literature Review - Kaptur, Agata; Dziedziński, Dawid; Łoś, Dawid; Nowak, Aleksandra; Janus, Anita (Quality in Sport, 2024)
The interplay between smoking and general anesthesia encompasses significant perioperative risks and complications. This comprehensive review evaluates the physiological consequences of smoking that challenge anesthetic management, including its effects on respiratory and cardiovascular system. We also analyse the impact smoking has on the metabolism of medications commonly used during anasthesia. Common complications of general anesthesia exacerbated by smoking are presented. The review elaborates on the Society for Perioperative Assessment and Quality Improvement 2020 guidelines for preoperative smoking cessation, emphasizing the timing and intensity of interventions, the use of pharmacotherapies, and the benefits of a multidisciplinary approach for improving patient outcomes. Findings underscore the importance of early smoking cessation, which reduces respiratory complications. E-cigarettes as a smoking cessation aid are discussed. Lastly, the paper calls for vigilance in the perioperative management of smokers and the integration of cessation initiatives as a potential "teachable moment" for long-term abstinence.